Enhancement of Aged and Denatured Fingerprints Using the Cyanoacrylate Fuming Technique Following Dusting with Amino Acid‐Containing Powders. Issue 2 (14th January 2013) - Nixon, Carly; Almond, Matthew J.; Baum, John V.; Bond, John W.
Abstract : We have carried out experiments to investigate the aging of latent fingerprints deposited on black PVC over a period of 4–15 weeks. A thumbprint was used in each case and before deposition of the print the donor rubbed their thumb around their nose to add sebaceous deposits. We have studied the effect of heat, light, and moisture and we find that moisture is the most significant factor in the degradation of the latent print. We have attempted to enhance these latent prints by dusting with valine powder or powders composed of valine mixed with gold or red fluorescent commercial fingerprint powders. To make a direct comparison between "treated" and "untreated" prints, the prints were cut in half with one‐half being "treated" and one‐half not. Our studies show the best results being obtained when powders of valine and red fluorescent powders are applied prior to cyanoacrylate fuming.